English for accounting - Frendo, Evan (Oxford University Press, 2007)
This book has been specifically developed for people working in accounting and finance who need English to communicate in a variety of situations with colleagues and business partners. In this short course, you will learn the language related to accounting as well as ways to achieve your goals in meetings, in presentations, on the telephone, or when making small talk.